Analisis Pengelolaan Keuangan Startup Dalam Mencapai Keberlanjutan Bisnis - Zebua, Melki Setiawan (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze how effective financial management plays a role in maintaining startup business sustainability amidst a volatile ecosystem. Many startups fail within the first two years due to poor cash flow management (high burn rate). The method used is descriptive qualitative, reviewing the literature and case studies of several technology startups. The results indicate that financial reporting transparency, efficient capital allocation, and diversification of funding sources are key pillars of sustainability. The study's conclusion emphasizes that startups must shift their focus from mere growth to sustainable profitability.